Investigation of high-speed deep well pump performance with different outlet setting angle of space diffuser - Gao, Yang; Cao, Weidong; Zhang, Yangjie; Cao, Gang; Zhao, Xiaojie (Frontiers in Energy Research, 2023)
As one of the important equipment for pumping groundwater, how to improve the operation performance of deep well pump has been a research hotspot. At present, most of the deep well pump hydraulic design research mainly focuses on the low speed condition, and there is still a lack of systematic research on the internal flow theory and design method of the high speed deep well pump. In this paper, numerical simulation is used to investigate the performance change law of high speed deep well pump under different space diffuser blade outlet setting angles, and the performance test of the design scheme model is used to verify the accuracy of numerical simulation. The hydraulic loss inside the space diffuser and the velocity moment at the outlet are quantitatively analyzed. The results shown that the outlet setting angle of 90° is a relatively optimal solution. Under the designed outlet setting angle, the hydraulic loss in the first-stage space diffuser decreases with the increase of the flow rate, and the average hydraulic loss in the space diffuser at all levels fluctuates between 16% and 20%. With the increase of the number of stages, the velocity moment at the outlet of the space diffuser also increases gradually, and the change trend of the velocity moment at the outlet of the first-stage space diffuser under different outlet setting angles is relatively consistent. This research can provide reference for the optimal design and application of high speed deep well pump.